Parmotrema sahyadrica (Parmeliaceae): A new species of parmelioid lichen from Wayanad, Southern Western Ghats, India - Sequeira, Stephen; Christy, Arun; Anilkumar, Aswathi; Arsha, S. M. (Phytotaxa, 2022)
A new species of Parmotrema with characteristic yellow medulla is described as new to science. The new species P. sahyadrica has a densely isidiate thallus with 6-10 mm wide lobes and contains entothein and atranorin as major compounds. The material was collected from Wayanad district of Kerala state at an elevation of 750 m.